Matchmaking in Sunan Giri Salatiga Islamic Boarding School: A Review of J.S. Mill's Utilitarianism - Muhammad Ova Lutfi Badrul Huda; Ali Geno Berutu (QURU’: Journal of Family Law and Culture, 2024)
This article analyses the concept of utilitarianism proposed by J.S. Mill and its application in the context of arranged marriages at Sunan Giri Islamic Boarding School in Salatiga. Furthermore, the purpose of this research is to analyse an arranged marriage that occurs in an Islamic boarding school using the theory of utilitarianism presented by J.S. Mill.  The research applied is field research with a qualitative method that is descriptive analytical, and uses a phenomenological approach using J.S Mill's theory. Data was collected through interviews conducted with the parties involved both online and offline, which in this case is the Kiai of the pesantren or Abah Rikul and senior students and students who have been successfully matched. It was found that in terms of the causes and effects of matchmaking that occurred in line with the ultimate goal to be achieved by utilitarianism. The results showed that the arranged marriage that occurred at Pondok Sunan Giri was actually to maintain the principles of utilitarianism, namely as follows: a) In the aspect of usefulness that arranged marriages are actually to maintain the dignity of the santri themselves. b) Then in the aspect of justice, that arranged marriages that occur at the cottage are democratic in which the final decision holder is fully in the approval of the prospective bride and groom, c) Then then there are individual interests. As a basic capital, to serve in the community, d) Then the last is the public interest. In this case it is contained in the purpose of matchmaking where according to Abah Rikul the matchmaking must be able to have a positive effect on the benefit of as many people as possible.